Anti-CII antibody as a novel indicator to assess disease activity in systemic lupus erythematosus. (November 2015) - He, C; Mao, T; Feng, Y; Song, T; Qin, C; Yan, R; Feng, P
Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder that affects a variety of organ systems. Anti-dsDNA Abs and complement factors have been used as indicators of lupus activity for more than 50 years. A novel indicator of activation in SLE is reported in this paper. Anti-collagen type II (CII) Ab was obviously elevated in patients with SLE compared to those patients with ankylosing spondylitis (AS) and healthy controls (HCs). Anti-CII-Ab-positive patients with SLE showed significantly higher levels of serum IgG and higher titers of ANA but lower levels of C3 and C4 than controls. A positive correlation was demonstrated between anti-CII Ab and serum IgG in SLE patients ( r = 0.50, p < 0.0001). The negative correlations of anti-CII Ab with C3 and C4 were observed in SLE patients ( r = –0.36, p = 0.0013; r = –0.37, p = 0.0006, respectively). The reduced anti-CII Ab level was accompanied by decreased level of serum IgG and increased levels of C3 and C4 after regular treatment. Therefore, anti-CII Ab could be a novel indicator for monitoring activity of SLE.